Cryptanalysis of a non-interactive protocol for member expansion in a secret sharing scheme - XU Jing-fang1; CUI Guo-hua1; CHENG Qi2; ZHANG Zhi1 (Tongxin xuebao)
Cryptanalysis of a non-interactive protocol for member expansion in a secret sharing scheme was presented, in which a malicious broadcast receiver might easily recover old t shares, new share and further reconstruct the secret S. The claimed security could not be realized. In addition, a new protocol was proposed, which elaborately eliminates the defect of previous protocol and improved the efficiency of existing schemes.